Captain Underpants and the sensational saga of Sir Stinks-a-Lot : the twelfth epic novel - Pilkey, Dav, 1966- (Pilkey, Dav, 1966-. Captain Underpants, 2021)
George and Harold, and their doubles, Yesterday George and Yesterday Harold, have a good thing going. Two of them go to school, while the other two hide in the tree house and play video games all day-then they switch! But when their malicious gym teacher, Mr Meaner, creates a method of mind control that turns their fellow students into attentive, obedient, perfect children, the future of all humanity will be in their hands!